1999
DOI: 10.2307/249750
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Information Technology Infrastructure for Business Process Redesign

Abstract: Kata kunci: IT infrastructure, IT services, business process redesign and reengineering, business strategy, IT alignment Masalah:Business Process Redesign (BPR) merupakan alat yang tepat tetapi sekaligus menantang untuk merubah suatu organisasi. Pada BPR, infrastruktur teknologi informasi (TI) memiliki peranan yang penting, karena dapat menentukan keberhasilan dari BPR tersebut. Tujuan:Artikel ini bertujuan untuk menunjukkan sejauh mana infrastruktur TI berkontribusi terhadap suksesnya implementasi BPR di dala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
244
0
18

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(265 citation statements)
references
References 22 publications
3
244
0
18
Order By: Relevance
“…Information is vital to all business processes that make up an organization's operations and management (Chaffey & Wood, 2005), therefore it should not be a surprise, that business process renovation research demonstrated the critical role of information technology in business process renovation (Broadbent et al, 1999). Nowadays information technology (IT) offers very good solutions for implementing business process renovation.…”
Section: Business Processes and Business Process Renovationmentioning
confidence: 99%
“…Information is vital to all business processes that make up an organization's operations and management (Chaffey & Wood, 2005), therefore it should not be a surprise, that business process renovation research demonstrated the critical role of information technology in business process renovation (Broadbent et al, 1999). Nowadays information technology (IT) offers very good solutions for implementing business process renovation.…”
Section: Business Processes and Business Process Renovationmentioning
confidence: 99%
“…IT is considered as an applicable complementary device in reengineering projects and the driving force which would support the business processes. Any process should be designed in correspondence with IT capacities (Broadbent, Weill, & St. Clair, 1999). …”
Section: The Six Stages In Methodologiesmentioning
confidence: 99%
“…A fourth dimension, IT infrastructure, was included later, and has been studied by several authors (Broadbent and Weill, 1997;Broadbent, Weill, and Neo, 1999;Broadbent, Weill, and ST Clair, 1999;Weill, Subramaniand Broadbent, 2002). Initial research defines IT infrastructure by the IT components, the human part, the shared IT services.…”
Section: The Dimensions Of Itpmmentioning
confidence: 99%